Cumulative Violence and Post-Traumatic Stress: An Integrative Model of Coping and Resilience Among Women Exposed to Sexual and Conflict-Related Violence - Naama Bar; Stav Shapira; Orna Braun-Lewensohn (European Journal of Investigation in Health, Psychology and Education, 2025)
This study explored how exposure to sexual and conflict-related violence relates to the severity of post-traumatic symptoms and how personal and community resilience factors and coping strategies mediate that relationship. Self-report questionnaires were completed by 568 Israeli women, who were classified into four exposure groups: (a) high sexual violence, (b) high conflict-related violence, (c) dual high exposure, and (d) low exposure. Significant differences were found between the group exposed solely to conflict-related violence and the groups exposed to sexual or both kinds of violence. Those who had been exposed to both types of violence reported lower levels of a personal sense of coherence, greater use of non-adaptive coping strategies, and more severe post-traumatic symptoms, as compared to the high conflict-related violence group and the low-exposure group. The dual-high-exposure group also reported lower levels of community resilience than the high-conflict-related-violence group and less use of adaptive coping strategies than the high-sexual-violence group. The severity of post-traumatic symptoms was explained by combined exposure to both sexual and conflict-related violence, personal resilience, and the use of non-adaptive coping strategies. These findings emphasize the unique psychological burden associated with intersecting exposures.